An Efficient IoT Enabled Smart Ambulance Routing Appling LOADng Routing Protocol: Aiming to Achieves Sustainable Development Goals - Nila Sultana, Methila Farzana Woishe, Tamanna Zaman Bristy, Dr.Md. Taimur Ahad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Despite, the fact, Internet of Things (IoT) has been applied in traffic detection and vehicle safety very few research shed light on how IoT-based smart transportation can achieve SDGs goals. Moreover, IoT inherits limitations from the power of the devices in the IoT infrastructure. Such limitations demand the need to have optimization research.To fill this gap,firstly this research applied LOADng-IoT protocol for the ambulance route system and secondly discussed how the system can be aimed to achieve SDGs goals. This research is significant, as traffic jam has become the main challenge in current metropolitan cities. Both in developed and developing nations, it is a concern for an ambulance to carry an emergency patient. Despite the fact, ambulance receives special traffic protocols, it is still challenging that the ambulance reaches the hospital on time. Lastly, the system is discussed under the lanes of the SDGs goals and pinpoints to the SDGs targets that can be achievable by this study.